Psychometric properties of the SocioEmotional Skills Instrument for Teachers using network approach: English and Spanish version - Sáez-Delgado, Fabiola; Mella-Norambuena, Javier; López-Angulo, Yaranay (Frontiers in Psychology, 2024)
The importance of socioemotional teaching skills has been highlighted for its link with better academic, social, emotional, and behavioral results of students, as well as for its contribution to work wellbeing, mental health and prosperity of teachers. However, there are few instruments that measure these skills in teachers in the context of their professional practice. The purpose of this research was to analyze the psychometric properties of the SocioEmotional Skills Instrument for Teachers (SEMS-IT). An instrumental design and a sample of 853 Chilean secondary school teachers were used. To evaluate the dimensional structure of the instrument, a portion of the sample (n = 468) underwent a network estimation method with Exploratory Graph Analysis (EGA) using a Gaussian GLASSO model. Then, in order to confirm the structural consistency and stability of the items, the analysis was replicated in a second sample (n = 385), where these results were additionally contrasted with those of the CFA analysis. The EGA findings confirmed a structure of 4 dimensions and 19 items in total: (a) Cognitive Management of Teacher Emotion (4 items); (b) Teacher Empathic Concern (4 items); (c) Teacher-Student Relationship (4 items); and (d) Adverse Classroom Climate (7 items), with a 7-point Likert scale response format. The CFA showed good and acceptable fit indicators, X 2 (171) = 354.546 (p < .001), CFI = .971, TLI = .966, RMSEA = .061 and SRMR = .062. In conclusion, a tool for the assessment of teachers' socioemotional skills, valid for school-based educational research, is provided. Implications of the findings at the theoretical and practical levels are discussed, as well as limitations and future projections for future research.